Resolution on the Implementation of Extracurricular Scouting Education at the East Jakarta Sub-District Council - Siti Wahyuni; Fadjriah Hapsari; Prasetio Ari Wibowo; Mirna Herawati (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2025)
This study aims to explore how Scouting extracurricular programs are implemented in several elementary schools in East Jakarta and what factors influence their effectiveness. Using purposive sampling, three schools in the Lubang Buaya area were selected, with data gathered through interviews, documentation, and questionnaires involving principals, curriculum vice principals, and Scout Leaders. Data were analyzed using source and technical triangulation. Findings show that Scouting plays a significant role in shaping character and strengthening Pancasila values (P5) through Dasadharma and Satya Pramuka. Two schools (SDN 06 and SDN 012) were effective in terms of human resource input, supported by complete coaching teams for each level. Only one school met the criteria for facilities and equipment, although all had adequate outdoor training areas. In terms of budget allocation (RKAS), only SDN 06 documented Scouting expenses. Academic demands and limited parental or environmental support remains key obstacles to program implementation.